Feasibility Assessment of a Microfluidic Chip Platform for SH-SY5Y Cell Culture under Static Conditions - Gözde Narin; Mehmet Yüksekkaya; Onur İnam; Meriç Arda Eşmekaya (Journal of Gazi University Health Sciences Institute, 2026)
Establishing baseline biocompatibility under static conditions is essential before dynamic perfusion studies. This study evaluates whether a custom microfluidic platform can support neuronal cell culture under controlled static conditions. A custom PMMA-glass microfluidic chip was evaluated for SH-SY5Y neuroblastoma cell culture, using a conventional polystyrene flask as a control to compare substrate compatibility under equivalent conditions. Cells were cultured statically for 24 hours with equivalent cell density and volume (12,000 cells; 64 µL). Morphological observations assessed cell adhesion, spreading, and structural characteristics. For quantitative analysis, cells were manually counted from randomly acquired microscopy images (representing technical replicates) and mathematically extrapolated to the total 32 mm² culture area. Visual evaluations confirm homogeneous cell distribution with characteristic neurite-like extensions across both surfaces. From the initial 12,000 cells, the extrapolated final cell count was 17,967 for the conventional flask and 18,691 for the microfluidic chip. This demonstrates comparable cell attachment and a slightly higher cell yield on the chip platform. The PMMA-glass microfluidic chip provides a biocompatible microenvironment that supports SH-SY5Y cell attachment and a comparable increase in observed cell number under static conditions relative to conventional polystyrene. These results validate the platform's suitability for neuronal cell culture, establishing a robust foundation for future dynamic, perfusion-based neurobiological studies.